RE-ENGINEERING JAKARTA CITY INTO A SUSTAINABLE AND RESILIENT GLOBAL CITY BASED ON CONTEMPORARY PUBLIC POLICY - Teguh Yuwono; K.P.Suharyono Soemarwoto Hadiningrat (Yayasan Inspirasi Merah Putih Indonesia, 2024)
The relocation of the capital of Indonesia from Jakarta to the archipelago has the consequence of reengineering Jakarta into a specific city referring to the dynamics and aspirations that develop as the embodiment of contemporary public policy. Where the aspirations of the community are one of the important considerations that will be taken by the central government and the Jakarta Special Region government. The change of Jakarta's status from the Special Capital Region of Jakarta to the Special Region of Jakarta must be determined in any case, so that there is no overlap in its implementation. It is appropriate to make Jakarta a sustainable and resilient Global City in line with the aspirations of the community and global dynamics that change very quickly in response to the humanitarian crisis, food and energy crisis, so it is necessary to commit together to carry out sustainable and resilient development to meet the needs of the current generation and prepare the needs for future generations. The potential is so great that according to the 2023 Global City Index (CGI), Jakarta ranks 74th out of 156 global cities in the world. The globality of a city can be seen, among others, from the economic sector, research and development, multicultural interaction, ease of life, nature and environment, and the accessibility of its citizens. Then, by referring to the experience of other countries that separate the center of government from the center of business, it is appropriate that the city of Nusantara becomes the center of government and the city of Jakarta becomes the center of international business; such as Sejong City (government center) and Seoul City (business center) in South Korea. In relation to contemporary public policy, it is dynamic depending on many factors, including changes in people's aspirations and demands to the government, campaign promises of Presidential Candidates/Vice Presidential Candidates, campaign promises of Presidential Candidates-to the regions, openness and courage of the public to express their opinions in public, the establishment of democracy and public participation. The issue of city globalization is related to 7 (seven) dimensions of economy, research and development, multicultural interaction, ease of life, nature and the environment, and accessibility of its citizens. And sustainable development has 17 (seventeen) goals, namely: a) Without poverty; b) No hunger; c) Healthy and prosperous life; d) Quality education; e) Gender equality; f) Clean water and proper sanitation; g) Clean and affordable energy; h) Decent work and economic growth; i) innovation and infrastructure industries; j) Reducing the gap; k) Sustainable cities and settlements; l) Responsible consumption and production; m) Handling climate change; n) Ocean ecosystems; o) Terrestrial ecosystems; p) Peace, justice and resilient institutions; and q) Partnerships to achieve goals. Then, urban resilience is the capacity of individuals, communities, institutions, businesses, and systems within a city to survive, adapt, and grow, regardless of the type of chronic stress and acute shock they experience; where in May 2016, the City of Jakarta was selected as a member of the 100 RC (Resillient City) network. The results of this study conclude that the central government and the DKJ government to re-engineer the city of Jakarta into a sustainable and resilient Global City. And it is recommended to the Central Government and the Jakarta Government to collaborate in realizing the City of Jakarta to become a sustainable and resilient Global City, after the City of Jakarta does not become the Capital of the State.